This is already in the required form (since the x-terms are together with dx terms, and y-terms are together with dy terms), so we simply integrate:

`inty^2dy+intx^3dx=0`

Giving:

`y^3/3+x^4/4=K`

This is the **general solution** for the differential
equation.

We can continue on to solve this as an explicit function in x, as follows:

`y^3=3(K-x^4/4)`

`y=root(3)(3(K-x^4/4))`

Taking a typical constant value `K=5`, we have this solution graph:

Typical solution graph `y=root(3)(3(5-x^4/4))`.

Easy to understand math videos:

MathTutorDVD.com